2005
DOI: 10.1590/s0100-879x2005001000010
|View full text |Cite
|
Sign up to set email alerts
|

The prima donna of epigenetics: the regulation of gene expression by DNA methylation

Abstract: This review focuses on the mechanisms of DNA methylation, DNA methylation pattern formation and their involvement in gene regulation. Association of DNA methylation with imprinting, embryonic development and human diseases is discussed. Furthermore, besides considering changes in DNA methylation as mechanisms of disease, the role of epigenetics in general and DNA methylation in particular in transgenerational carcinogenesis, in memory formation and behavior establishment are brought about as mechanisms based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 54 publications
0
31
1
2
Order By: Relevance
“…Methylation, a covalent chemical modification of DNA, is catalyzed by DNA (cytosine-5) methyltransferases (DNMTs) and, together with other modifications affecting chromatin structure, DNA methylation serves to regulate gene transcription. DNA methylation has been studied extensively in development, and has long been considered a static process following cell differentiation (Santos et al, 2005). However, high DNMT mRNA levels persist into adulthood in the brain and we have found that DNMT inhibition alters gene methylation in vitro and in vivo and prevents the induction of LTP and the consolidation of memory (Levenson et al, 2006;Miller and Sweatt, 2007).…”
mentioning
confidence: 69%
“…Methylation, a covalent chemical modification of DNA, is catalyzed by DNA (cytosine-5) methyltransferases (DNMTs) and, together with other modifications affecting chromatin structure, DNA methylation serves to regulate gene transcription. DNA methylation has been studied extensively in development, and has long been considered a static process following cell differentiation (Santos et al, 2005). However, high DNMT mRNA levels persist into adulthood in the brain and we have found that DNMT inhibition alters gene methylation in vitro and in vivo and prevents the induction of LTP and the consolidation of memory (Levenson et al, 2006;Miller and Sweatt, 2007).…”
mentioning
confidence: 69%
“…The more restricted transgene expression in adult mice possibly reflects differences in gene regulation between embryonic and adult tissues. 39 To confirm that it was the Ϫ5.5HS that conferred EC specificity to the 6-kb hEPCR promoter, Ϫ5.5HS was coupled to the heterologous SV40P. In transgenic embryos, high-level reporter gene expression was reproducibly directed to ECs, demonstrating that, by itself, the Ϫ5.5HS enhancer contains the regulatory sequences necessary to impart vascular specificity and thus functions as an autonomous EC-specific enhancer.…”
Section: Discussionmentioning
confidence: 98%
“…Methylation of cytosine nucleotides on DNA itself is the so-called 'fifth-base' of DNA and the 'prima donna' of the epigenetic landscape (Santos et al, 2005). This modification is catalyzed by DNA methyltransferases (DNMTs), which are divided into two groups (see Figure 2).…”
Section: Methylation and Demethylationmentioning
confidence: 99%